Curriculum Management in Building the Branding of the Institute of Islamic and Arabic Studies (LSIA) in the Digital Era - Hayat, Nisa Khoerotul; Rubini (The Faculty of Education and Teaching Training, 2025)
This study aims to examine the planning and implementation of the curriculum at the Institute of Islamic and Arabic Studies (LSIA) as a response to the needs of students who are oriented towards studying in the Middle East. The approach used is descriptive qualitative, with data collected through interviews, observations, and documentation studies. The results of the study indicate that the LSIA curriculum is designed holistically, adaptively, and participatory, involving various stakeholders. The design is based on three main pillars: philosophical-religious values, adolescent development psychology, and international academic standards. The implementation of the curriculum reflects the integration of classical and digital learning media, as well as contextual methods such as talaqqi, muhadatsah, and khitobah. Evaluation is carried out periodically and incidentally to ensure dynamics and relevance. The learning strategy is individual, with initial mapping, remedial classes and acceleration. Hidden curriculum such as tahfiz, ruhiyah bina malam, and social activities contribute to the formation of Islamic character. In addition to being a pedagogical tool, the curriculum is used as a strategy to build the image and reputation of the institution. LSIA utilizes social media, alumni networks, and national and international forums to strengthen branding as a valuable, locally relevant, and globally competitive Islamic educational institution. This study fills the gap in studies that link curriculum management and institutional communication strategies, and offers a practical model of curriculum management as an academic instrument as well as branding of institutions based on Islamic values.